Children’s Transformative Agency in Computational Play – Imagine, Improvise and Influence - Kaup, Camilla Finsterbach; Fredskilde, Pauline; Møller, Anders Kalsgaard (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2025)
This article explores how young children enact agency through computational play in a Danish kindergarten. Drawing on sociocultural theory, transformative agency, and participation trajectories, the study examines how children engage with computational thinking through unplugged, play-based activities. Using video and field ethnography, the study shows how children observe, improvise, and reconfigure tasks, embedding computational concepts like sequencing and decomposition in playful ways. Rather than following predefined goals, children reshape activities on their own terms. The study highlights computational play as a relational space for agency and co-exploration, expanding computational thinking beyond skill acquisition and toward imaginative, situated engagement.